Interplay of Corporate Sector, Politics, and Media in Shaping News Contents in Nepal - Pandey, Lekhanath (Baneshwor Campus Journal of Academia, 2024)
This paper examines the intricate implications arising from the symbiotic relationship among the corporate sector, politics, and media in shaping news content in Nepal. This study analyzes the dynamics and interplay between politics, corporate sectors and the influence they can have on the media content largely within the privately run for-profit media outlets in Nepal. The theoretical foundation for this study has been rooted in Habermas’ public sphere model of mass media (1989). The study revealed that vested corporate and political interests are hugely influential both in shaping the opinion and performance of the news media. Besides, the corporate influence, the ideological division of media outlets and journalists not only raises ethical concerns but also the quality of discourse. Taken together, they only undermine the very credibility of the media institutions which does not allow them to become what Habermas calls the public sphere.